Application of Physical Eduation Subjects to the Development of Student Character Values - Maharani Fatima Gandasari (Indonesian Journal of Sport Management, 2023)
Implementing physical education in developing students' character values ​​not only influences their personal development but also positively contributes to a better society. Applying physical education in character formation affective attitudes, starting from discipline, honesty, responsibility and socializing well. This research has the aim of producing the application of physical education in building student character. The approach used by researchers in this research is descriptive-quantitative. The sample used was 200 junior high school students in Ngabang District, namely SMPN 1, SMPN 2, SMPN 3; Maniamas Middle School; Macedonia Christian Middle School; and Pelita Middle School. The questionnaire is the research instrument used by researchers. The questionnaire was then tested for validity to see the student's character in the initial and final conditions for all items so that it could be declared valid and reliable. The author analyzed the data using the t-test. The research results show the initial condition of the character values ​​of junior high school students in Ngabang District. The score in the initial condition of the student's character was 85,67%, while the final condition score was 80,68%, so the researchers concluded that there had been an increase of 11,36%. The conclusion obtained by researchers is that physical education learning has the content of developing character values ​​, which can improve students' character. The suggestion given by the researcher is that teachers must have a policy that implements the development of character values ​​in every subject.